Mapping of the Transportation Sector in Maluku Province Using Biplot Analysis - Leleury, Zeth Arthur; Radjabaycolle, Jefri Esna Thomas; ilwaru, Venn Y. I.; Sinay, Lexy Jansen; Wattimena, Abraham Z. (Tensor: Pure and Applied Mathematics Journal, 2024)
The transportation sector is one sector that contributes to economic development. Economic activity will develop if it has good infrastructure and transportation facilities for accessibility. This study aims to map regencies/cities in Maluku province based on the characteristics of the transportation sector. The method used is Biplot analysis. Based on the results of the study, it was found that the results of mapping 11 regencies/cities in Maluku Province if grouped according to the location of the quadrant divided into 2 clusters, namely Cluster 1 consisting of the City Ambon, West Seram Regency, Central Maluku Regency, Buru Regency, Tual City, Southeast Maluku Regency, and Tanimbar Islands Regency. The seven regencies/cities have similar characteristics of the transportation sector in the percentage of villages where public transportation is available with fixed routes, the widest type of land surface is asphalt/concrete, and the road can be passed by four wheels throughout the year. While Cluster 2 consists of Eastern Seram Regency, South Buru Regency, Southwest Maluku Regency, and Aru Islands Regency. The four regencies have similar characteristics of the transportation sector in the percentage of villages based on the availability of land and sea transportation infrastructure, the availability of sea transportation infrastructure only, public transportation is not available or available without a fixed route, the widest type of land surface is in the form of soil or hardened with gravel, the road cannot be passed by four wheels or four wheels can pass but only in the dry season. Meanwhile, based on the Euclidean distance, it can be made more specific into 4 clusters, namely Cluster 1 is Ambon City, Cluster 2 includes West Seram Regency, Central Maluku Regency, Buru Regency, Tual City, Southeast Maluku Regency, and Tanimbar Islands Regency. Meanwhile, Cluster 3 includes Eastern Seram Regency, South Buru Regency, and Southwest Maluku Regency, and Cluster 4 is Aru Islands Regency.